IDDF2018-ABS-0266 Aggressive multimodality therapy in extra gastrointestinal stromal tumour can have prolonged survival; a case report. (June 2018) - Das, Satyabrata; Chaturvedi, Arun; Mishra, Sanjeev; Kumar, Vijay; Gupta, Sameer; Akhtar, Naseem; Rajan, Shiv; Prakash, Puneet; Mukherjee, Saurabh
Abstract : Background: Extra Gastrointestinal Stromal Tumour (EGIST) is a rare clinical entity with aggressive biological behaviour. Only few case reports have been published in the literature. We present a case of malignant EGIST who have prolonged survival with multimodality therapy involving surgery and targeted therapy. Methods: A 39 year female presented to our outpatient department in May 2016 with complaints of pain in the abdomen. The patient had a history of laparotomy in 2011 for a benign ovarian cyst. Eighteen months later She was diagnosed as a case of GIST and was on treatment with imatinib 400 mg/day. The patient was asymptomatic until in 2016 she developed pain abdomen. On clinical examination, there were palpable lumps involving umbellical and right iliac fossa. CECT showed a hetrogenous complex cystic mass in pelvis along with multiple omental and parietal wall nodules. The core biopsy suggested Malignant GIST positive for CD117, SMA and vimentin. CD34 was negative and Ki 67 was 60%. The patient was given Imatinib at a dose of 800 mg/day in divided doses. After five months of treatment, the patient had a good response but had intermittent lower abdominal cramps for which she was planned for surgery. Total Abdominal Hysterectomy with bilateral salpingo-oophorectomy, omentectomy and peritonectomy was done. Surgical recovery was good, and the patient was given imatinib 800 mg/day. Results: Post surgery histopathology also suggested Malignant Extra intestinal GIST with IHC similar to the core biopsy. The patient was compliant with therapy, and there was no comorbidity till the last follow update in February 2018.Post surgery patient was disease free for fourteen months and overall 61 months from the initial diagnosis. Conclusions: Extra Gastrointestinal Stromal Tumour is a rare disease, and no standard treatment guideline is available. Imatinib forms. The backbone of treatment and surgery is indicated for localised disease. In our case, aggressive surgery after a good response to Imatinib has resulted in longer survival. Although more data is required aggressive surgery with Targeted therapy seems promising.